Positivity and Risk Factors for Trichomonas vaginalis Among Women Attending a Sexual Health Clinic in Melbourne, 2006 to 2019. Issue 11 (10th November 2022) - Abraham, Esha; Fairley, Christopher K.; Denham, Ian; Bradshaw, Catriona S.; Farquharson, Rebecca M.; Vodstrcil, Lenka A.; Plummer, Erica L.; Ong, Jason J.; Chen, Marcus Y.; Phillips, Tiffany R.; Chow, Eric P.F.
Abstract : The positivity of Trichomonas vaginalis is rising in female clients in Melbourne, Australia. Associated factors include concurrent syphilis, concurrent chlamydia, injecting drug use in the last 12 months, and age of at least 35 years. Abstract : Background: Trichomonas vaginalis is not a notifiable disease in Australia in most states, resulting in limited Australian epidemiological studies. This study aimed to examine the positivity of T. vaginalis in women attending the Melbourne Sexual Health Centre (MSHC) and identify associated factors. Methods: All women 16 years or older who were tested for T. vaginalis at MSHC from 2006 to 2019 were included. The diagnostic method changed from culture to nucleic acid amplification test in August 2018. The annual positivity of T. vaginalis was calculated. Because of the data completeness, we performed a generalized estimating equations multivariable logistic regression using data from 2011 to 2019 to examine factors associated with T. vaginalis positivity. Results: From 2006 to 2019, 69, 739 tests for T. vaginalis were conducted, and 294 tested positive (0.42%; 95% confidence interval [CI], 0.37%–0.47%). Approximately 60% of women tested reported symptoms. After adjusting for potential confounders including the change in diagnostic method, there was a 21% (95% CI, 12%–31%) annual increase in T. vaginalis positivity between 2011 and 2019. Women with concurrent syphilis had the highest odds of testing positive for T. vaginalis (adjusted odds ratio [aOR], 21.55; 95% CI, 6.96–66.78), followed by women who had injected drugs in the last 12 months (aOR, 6.99; 95% CI, 4.11–11.87), were 35 years or older (aOR, 3.47; 95% CI, 2.26–5.35), or had concurrent chlamydia (aOR, 1.77; 95% CI, 1.05–2.99). Conclusions: The rising positivity of T. vaginalis at MSHC irrespective of change in diagnostic method suggests a concurrent community-wide rise in Melbourne. Given the rising positivity, testing informed by risk factors should be considered.